Desain e-modul Biologi Berbasis Education for Sustainable Development (ESD) Terintegrasi Etnosains Dalam Mendukung Implementasi Deep Learning - Erlia Hanum; Zainatul Hasanah; Cut Roswita (Jurnal Penelitian Pendidikan IPA, 2026)
This research aims to developing a biology e-module based on education for sustainable development (ESD) integrated with ethnoscience and analysing the developed product’s validity and practicality. This research is a research and development (R&D) with the ADDIE development model. This research was conducted at SMAN 1 Bireuen and SMAN 1 Peusangan. Data collection instruments and techniques used expert validation test and questionnaires. The expert validation was used to measure the validity of the developed e-module. The questionnaire was used to measure the practicality of the developed e-module. Data analysis was carried out by processing validator responses and Likert scales. The validity test results showed that the average Aiken Index (V) of biology e-module based on ESD integrated with ethnoscience according to media experts and media experts was 0.81 and 0.89, respectively, with the category of very valid. The average percentage of practicality test results for the biology e-module at SMAN 1 Bireuen and SMAN 1 Peusangan were 90.5% and 85.9%, with the category of very practical. It can be concluded that the biology e-module based on ESD integrated with ethnoscience is valid and practical for use as a teaching material to support the implementation of deep learning